Analysing cultural elements in L2 Mandarin textbooks for Malaysian learners - Lin, Wen Yue; Ang, Lay Hoon; Chan, Mei Yuit; Paramasivam, Shamala (National Research University Higher School of Economics, 2020)
Culture is an important aspect of foreign or second language education as the teaching of foreign languages straddles two languages, the learner’s first language and the target/foreign language, and the different cultures associated with them. Textbooks for the teaching of foreign languages must inevitably orient to cultural elements from at least two cultural practices and environments. In this study, cultural elements in four Mandarin as a second language textbooks written by Malaysian authors were examined using content analysis. The conception of cultural elements proposed by Zhang and Chen and the categorizations of types of culture proposed by Cortazzi and Jin and Chao were employed to investigate the extent to which cultural elements (knowledge-culture or communicative-culture) and types of culture (source, target, international cultures or intercultural interaction) are represented in these textbooks. The analysis found that both knowledge-culture and communicative-culture are embodied in the textbooks. Furthermore, most of the cultural elements identified in the textbooks represent source and target cultures which refer to learners’ own culture and culture of the target language. The presence of international cultures and intercultural interaction, on the other hand, is lower in these textbooks. This study contributes towards a better understanding of how Malaysian authors of Mandarin as a second language textbooks for Malaysian learners incorporate cultural elements in the books they write. It highlights the importance of integrating cultural elements and representing a diversity of cultures in textbooks for teaching Mandarin as a second language.